NEUROENDOCRINE CARCINOMA OF OVARY IN ASSOCIATION WITH MUCINOUS CYSTADENOMA - Rahim, Rehana; Faiz, Nasreen Ruby (Journal of Postgraduate Medical Institute, 2011)
A case of Neuro-endocrine carcinoma of ovary has been discussed. This thirty years old patient presented with mass in lower abdomen which was diagnosed to be an ovarian tumour .She had laparotomy and biopsy report was neuroendocrine carcinoma. She had two courses of chemotherapy and then did not come for follow up.